Analisis Model Blended POE2WE Terhadap Keterampilan Proses Sains Siswa Melalui Penggunaan Laboratorium Virtual Pada Materi Dualisme Gelombang Partikel - Laelawati, Mutia; Nana, Nana; Sulistyaningsih, Dwi (Universitas PGRI Semarang, 2021)
Most natural phenomena in physics learning require students to understand conscientific knowledge, so to improve students' understanding requires a scientific approach. The skills that can be developed are the skills of the science process. To balance theory and practice, practical activities are required to practice the skills of the science process. . However, there have been some experiments in which processes and concepts are abstract - one of which is on particle wave dualisme material. This research aims to describe how poe2we blended models students' science process skills on particle wave dualism material through the use of virtual laboratories. This research method uses literature studies from previous research. The results showed that the poe2we blended model in the use of virtual laboratories in particle wave dualism material was found to be a science process skill in students.